Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan pada PT Newton Education Center: The Effect of Motivation and Work Discipline on Employee Performance at PT Newton Education Center - Olvy Anindya; Aan Rahman (CV Warnak Johanna Nusantara, 2026)
PT Newton Education Center is a manpower agency company focused on providing and placing professional workers. This study aims to analyze the influence of motivation and work discipline on employee performance, both partially and simultaneously. The study used a quantitative approach with multiple linear regression analysis and data processing using SPSS version 27. The sampling technique used non-probability sampling with a saturated sample method of 40 respondents. Data were obtained through observation, questionnaires, and literature review. The results showed that: (1) motivation does not have a positive and significant partial effect on employee performance, with a calculated t-value of 1.234 < t-table 2.026 and a significance value of 0.225 > 0.05; (2) work discipline has a positive and significant partial effect on employee performance, with a calculated t value of 5.853 > t table 2.026 and a significance value of 0.001 < 0.05; and (3) motivation and work discipline have a positive and significant simultaneous effect on employee performance, with a calculated F value of 43.395 > F table 3.252 and a significance value of 0.001 < 0.05.